Pengaruh Kinerja Keuangan Dan Struktur Kepemilikan Terhadap Pengungkapan Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2018)
ABSTRACTSaidatun Ulpah. The Effect of Financial Performance and Ownership Structure on Corporate Social Responsibility Disclosure on Mining Companies Listed on Indonesia Stock Exchange. Supervised by Lewi Malisan and Hj. Anisa Kusumawardani.This study aims to determine the effect of financial performance and ownership structure on the disclosure of social responsibility (CSR Disclosure). The sample in this study is a mining company listed on the Indonesia Stock Exchange during the observation period from 2013 to 2016. The sample size of 10 companies with as many as 40 observations. The variables in this study are financial performance proxyed using return on asset and return on equity, ownership structure represented by institutional ownership and managerial ownership which counted its influence to corporate social responsibility disclosure (CSR). The method used is the type of quantitative data, the method used is the method of documentation. The data were analyzed using Multiple Linear Regression Analysis.The results of this study indicate that only the variable of institutional ownership and managerial ownership have a significant effect on CSR disclosure. While the financial performance variables proxyed with return on asset and return on equity have no significant effect on CSR disclosure at mining companies listed in Indonesia Stock Exchange. (BEI).